From Gulag to Fairy Tales: Boris Sveshnikov as a Soviet Book Designer Between Nonconformist Art and Children’s Literature - Svetlana Efimova (RUS (São Paulo))
In the 1950s–1980s, working as children’s book designers enabled many Soviet nonconformist artists to have a recognized role within the system. This article introduces an interdisciplinary and intermedial perspective on Soviet children’s book illustration by focusing on the work of Boris Sveshnikov (1927–1998). The artist established his visual style while imprisoned in the Gulag. After his release and exoneration, he transferred this graphic aesthetics to the design of various volumes of fairy tales, both folk and literary ones, within the Soviet project of “world literature” for adults and children. Sveshnikov’s illustrations were rooted in three intertwined contexts: 1) his nonconformist art (camp drawings and later pointillism); 2) his deep interest in romantic and symbolist literature; and 3) Thaw-era book design, which foregrounded the visualization of literary texts through graphic illustrations and hand lettering. The analysis traces Sveshnikov’s engagement with fairytale worlds in image and text as a response to Gulag-wrought trauma and as an aesthetic counterpart to the loosening of socialist realism under conditions of political liberalization.